Structure and Ultrasonic Properties of Vanadium Tellurite Glasses Containing Copper Oxide - ABD EL-AAL, Nadia S.; AFIFI, Hesham A. (Archives of Acoustics, 2009)
The elastic properties of vanadium tellurite glasses, 65TeO2-(35-x)V2O5-xCuO, with different compositions of Copper (x=7.5 to 17.5mol% in steps of 2.5mol%) have been studied at room temperature (300K). The ultrasonic velocity measurements have been made, using a transducer having resonating frequency of 4MHz (both longitudinal and shear). The density, molar volume, and ultrasonic velocities show interesting features, which are used to explore the structural changes in the network. Elastic moduli, Poisson ratio, crosslink density, Microhardnes, and Debye temperature of the glasses have been determined using the experimental data. The composition dependence of the elastic properties explores useful information about the physical properties of the vanadium tellurite glasses doped with Copper. Quantitative analysis has been carried out in order to obtain more information about the structure of the glass under the study, based on bond compression model and the Makishima [ampersand] Mackenzie model. The observed results through ultrasonic non-destructive evaluation, investigate the structural changes and mechanical properties of the glass.